Do Institutional and Public Ownership Limit Classification Shifting in Indications of Financial Statement Manipulation? - Zahrina Ghassani Amalina; Abdul Rohman (Jurnal Akademi Akuntansi, 2024)
Purpose: This study aims to investigate the role of institutional ownership and public ownership in reducing  financial statement manipulation reports using the classification shifting method. Methodology/approach: This study uses a quantitative method and collects data from IDX and Bloomberg. Using purposive sampling Comapanies listed as 100 Compas Index during 2022 this study employs 98 companies as research sample. Data are then analysed using regression Warp-PLS 8.0. Findings: The result indicate that institutional ownership and public ownership significantly reduce financial statement manipulation utilising classification shifting method of the companies. Practical and Theoretical contribution/Originality: This research is expected to contribute in providing additional insights both theoretically and practically for policy makers and companies for an increase in more careful supervision to minimize the practice of classification shifting in financial statement manipulation. Research Limitation: The limitation of this research is the scope of the research which only looks at companies included in the Kompas 100 Index in 2022, which is a small representation of all companies listed on the Indonesia Stock Exchange.